ڕۆڵی ڕاگەیاندن لە گەشەپێدانی هۆشیاری تەندروستی و نەریتی خواردن لای منداڵ لە ڕوانگەی مامۆستایانی باخچە (توێژینەوەی هەڵێنجراو) - مصطفی, صابر بكر; حه‌مه‌ئه‌مین, ئه‌كره‌م فه‌ره‌یدون; الدین, هاژە ناجح محی (Sulaimani Journal for Humanities, 2023)
The aim of this study is to determine the role of media in developing health awareness among children from the perspective of kindergarten teachers, demonstrating the role of media in health awareness among children from the perspective of kindergarten teachers according to a number of variables from them: (sex, age, years of service and degree), from the perspective of kindergarten teachers, and determining the role of media on eating habits among children from the perspective of kindergarten teachers according to certain variables such as: (sex, age, years of service and degree). The researcher has used the descriptive survey method. The research community consists of all kindergarten teachers in Sulaymaniyah City, public and private, and their number was (1187) teachers. The sample of the study is (179) male and female teachers. The appropriate class was randomly selected. The tools used include both criteria (Media and Health Awareness and Media and Food Traditions). The researcher prepared it by making use of the previous studies, thus the total number of the items reached (51) items of (Media and Health Awareness) and (31) items of (Media and Food Traditions), and (13) experts in the field of media and education saw it. The most important statistical tools used are (Pearson's Correlation coefficient, anova equation, t. test and Spearman's law). The results showed that there is health awareness and eating habits among kindergarten children from the perspective of teachers, and media’s role is (4.%87), which plays a role in health awareness, and (88.6%), is its role in eating habits among kind .